Experiential learning, collaboration and reflection: key ingredients in longitudinal faculty development - Farrell, Laura; Buydens, Sarah; Bourgeois-Law, Gisele; Regehr, Glenn (Canadian Medical Education Journal, 2021)
Background: Longitudinal faculty development (LFD) may allow for increased uptake of teaching skills, especially in a forum where teachers can reflect individually and collectively on the new skills. However, the exact processes by which such interventions are effective need further exploration. Methods: This qualitative study examined an LFD initiative teaching a novel feedback approach attended by five family practice physicians. The initiative began with two 1.5-hour workshops: Goal-Oriented Feedback (as the teaching skill to be developed) and Narrative Reflection (as the tool to support personal reflection on the skill being learned). Over the subsequent six-months, the five participants iteratively applied the feedback approach in their teaching and engaged in narrative reflection at four 1-hour group sessions. Transcripts from the group discussions and exit interviews were analyzed using thematic analysis. Results: Iteratively trialing, individually reflecting on, and collectively exploring efforts to implement the new feedback approach resulted in the development of a learning community among the group. This sense of community created a safe space for reflection, while motivating ongoing efforts to learn the skill. Individual pre-reflection prepared individuals for group co-reflection; however, written narratives were not essential. Conclusion: LFD initiatives should include an emphasis on ensuring opportunities for iterative attempts of teaching skills, guided self-reflection, and collaborative group reflection and learning to ensure sustainable change to teaching practices.